Implementation of MBKM: Digitalization Project and Use of Library Software for Schools in Randangan Village, Pohuwato Regency, Gorontalo Province: Implementasi MBKM: Proyek Digitalisasi dan Penggunaan Software Perpustakaan untuk Sekolah-sekolah di Desa Randangan Kabupaten Pohuwato Provinsi Gorontalo - Paputungan, Frezy; Husain, Rustam (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
The Minister of Education and Science and Technology stated that MBKM will be continued with various improvements. The Independent Campus (MBKM) was initiated by the Minister of Education and Culture through the Regulation of the Minister of Education and Culture Number 3 of 2020 concerning National Standards for Higher Education, especially in articles 18 and 15, aiming to answer the challenges of the capacity of higher education institutions that have not been able to adapt quickly to prepare relevant and quality graduates with the presence of Industry 4.0. Based on this decision, Bina Mandiri University Gorontalo has participated in and run the MBKM program. However, the implementation is still limited so that the scope of implementation is only at one point and then affects the development of unsustainable programs. Related to the MBKM program, undergraduate students of Educational Technology have been trained and are able to design software, one of which is for libraries in schools. This was proven in the implementation of previous research entitled The Impact of MBKM Project-Based Learning on Problem Solving for Undergraduate Students of Educational Technology at Bina Mandiri University, Gorontalo. Considering that the MBKM program is important to run and its sustainability is expected, its implementation is very urgent. In coastal areas, especially schools in Randangan Village, Pohuwato Regency, Gorontalo Province, it is known that digitalization in the implementation of education has not been effective, so there needs to be digitalization of library software to support student learning activities outside school hours or on holidays. The purpose of this study is to implement MBKM: a digitalization project and the use of library software in schools in Randangan Village, Pohuwato Regency, Gorontalo Province.